Slide member and manufacturing method of slide member
The sliding member with a non-porous layer and resin composition addresses friction and heat issues in high-speed bearings, enhancing wear resistance and reducing energy loss, enabling higher rotational speeds and compact designs.
Patent Information
- Application Number
- JP2023096877
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2043-06-13
AI Technical Summary
Existing sliding bearings used in high-speed rotating machinery, such as EV motors and electric compressors, face issues with temperature rise, wear, and energy loss due to friction, especially in high-speed and harsh lubrication conditions, leading to premature failure and increased energy consumption.
A sliding member with a cylindrical metal base material featuring a porous layer covered by a resin composition sliding layer, where a non-porous layer is exposed in specific regions to reduce friction and heat generation, incorporating hard particle powders like a Laves phase composed of Co, Mo, and Si to enhance wear resistance and lubrication.
The solution effectively suppresses temperature rise and reduces energy consumption by minimizing friction and maintaining lubrication, enabling higher rotational speeds and extending the lifespan of bearings, while allowing for smaller and lighter designs.
Smart Images

Figure 2024178609000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a slide member and a method for manufacturing a slide member. [Background technology]
[0002] Currently, energy efficiency and CO 2 From the perspective of emissions, there has been a shift from conventional engine-powered automobiles to electric vehicles (EVs) powered by batteries and motors. The output of a motor depends on its rotation speed and torque, and by increasing the rotation speed, the torque can be reduced and the volume can be made smaller. Therefore, high-speed motors are essential for making parts smaller and lighter and more energy-efficient. In addition, there is an increasing need to make the electric compressors built into the drive motors smaller and lighter for car air conditioners, which support the comfort of automobiles.
[0003] The Automotive Power Transmission Technology Research Association (TRAMI), which brings together domestic automakers and other organizations, has announced that it will shift the focus of its research from internal combustion engines to electric vehicle (EV) motors and related technologies. Currently, the rotation speed of EV motors is mainly around 13,000 rpm, but it is predicted that in the near future this will reach 20,000 rpm or more, and research is being promoted with an eye on ultra-high rotation speeds of 30,000 to 50,000 rpm. In particular, EV drive motors and electric compressors are required to be able to rotate at high speeds in order to achieve both compactness and light weight as well as high output.
[0004] In rotating machines that support the main shaft of motors and compressors, elements such as bearings and seals that support the rotating body play an important role. The sliding surfaces of these machine elements deteriorate over time, causing an increase in the friction coefficient and wear. This causes the temperature to rise due to heat generation, and various parts of the rotating machine begin to deteriorate, eventually causing the machine to no longer function as intended and reaching the end of its life. In addition, if the oil that should be in the gap of the bearing supporting the rotating shaft leaks out or foreign matter gets mixed into the gap due to friction and heat generated by the high rotation of the motor, the temperature and vibration of the sliding surface will become abnormally high, and the surface of the sliding material will melt and seize. In this way, friction and wear are often the main causes of performance deterioration and failure of machine parts. In particular, the sealed refrigerant and refrigeration oil are used to lubricate the sliding bearings used in compressors, but the lubrication state changes greatly depending on the operating conditions of the compressor, and severe lubrication states such as when there is only a liquefied refrigerant or when the compressor is close to dry are assumed.
[0005] Therefore, in boundary lubrication environments where oil films are difficult to form due to high rotation speeds of drive systems, eccentric shafts, etc., plain bearings with excellent wear resistance and seizure resistance are required. Furthermore, since the dimensional accuracy of the bearing, such as the gap between the shaft and the bearing, the shape of the bearing inner diameter surface that comes into contact with the shaft, and the presence or absence of protrusions due to joints, greatly affects the machine life, plain bearings also require high assembly accuracy.
[0006] Furthermore, for the sliding bearings used in compressors, the environment around the bearings will become more severe due to restrictions on fluorocarbons and the switch to new refrigerants as part of measures to combat global warming, so even higher performance bearings are being demanded.
[0007] Patent Document 1 proposes using rolling bearings in locations requiring high speed rotation, such as automobile parts, etc. However, rolling bearings have a shorter lifespan than plain bearings, so there is a demand for longer-life plain bearings that can be used under high speed rotation.
[0008] The applicant of the present application has already proposed a seamless sliding member on the sliding surface and a manufacturing method thereof as a sliding member having excellent wear resistance and seizure resistance in the high-speed rotation range (Patent Application No. 2023-026107). [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2018-179049 A Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention has been made in consideration of the above points. The object of the present invention is to provide a sliding member in which the temperature rise in the high-speed rotation region is suppressed more than that of the sliding member proposed in Japanese Patent Application No. 2023-026107, and a method for manufacturing the sliding member. [Means for solving the problem]
[0011] The slide member according to the first aspect of the present invention comprises: A cylindrical metal substrate; A porous layer formed on the inner circumferential surface of the metal substrate; A sliding layer is provided to cover the porous layer, The porous layer is formed of a metal or an alloy composition, The sliding layer is formed of a resin composition, The resin composition is not present on a part of the inner circumferential surface, and the non-porous layer formed of the metal element or alloy composition is exposed in the region.
[0012] According to this embodiment, a region is provided in which the resin composition is not present on a part of the inner circumferential surface of the sliding member and the non-porous layer formed of a metal simple substance or an alloy composition is exposed. Since the resin composition is not present in the surrounding area and the non-porous layer does not contain a large number of voids like the porous layer, this region has a concave shape compared to the surrounding area and plays a role like a groove. When the sliding member is used, the inner surface of the groove does not contact the shaft that is the sliding object, which contributes to reducing heat generation due to friction. This suppresses temperature rise in the high-speed rotation area and improves the performance of the bearing itself. In particular, when lubricating oil or grease is present, the oil film formation on the sliding surface is maintained by the groove, so that further heat generation reduction is expected compared to use in a dry environment. In addition, the resin composition is not present on a part of the inner circumferential surface of the sliding member, and a non-porous layer formed of a metal or alloy composition is exposed, and no protrusions due to seams appear on the sliding surface, reducing the torque generated by friction at the seams. This contributes to reducing power consumption and energy loss, and therefore contributes to carbon neutrality. Furthermore, for bearings used in high-speed environments, such as EV motors and electric compressors, it will be possible to replace conventional rolling bearings with the sliding members according to this embodiment, leading to smaller and lighter designs. Furthermore, when a conventional sliding member having a seam on the sliding surface is applied to a motor or a compressor, an inner diameter cutting process (i.e., surface alignment of the inner surface at the seam portion) is required. However, in the sliding member according to the present embodiment, the resin composition is not present on a part of the inner peripheral surface of the sliding member, and an area is provided where a non-porous layer formed of a simple metal or an alloy composition is exposed. Therefore, no protrusions due to the seam appear on the sliding surface, and the inner diameter cutting process can be eliminated.
[0013] A slide member according to a second aspect of the present invention is the slide member according to the first aspect, The region is provided so as to extend from one end to the other end in the axial direction of the sliding member.
[0014] According to this aspect, the effect of reducing heat generation due to friction can be obtained continuously from one end to the other end in the axial direction, so that the temperature rise in the high speed rotation region can be further suppressed.
[0015] A slide member according to a third aspect of the present invention is the slide member according to the first or second aspect, In the sliding layer, hard particle powder containing a Laves phase composed of Co, Mo and Si is dispersed.
[0016] A slide member according to a fourth aspect of the present invention is the slide member according to the third aspect, The sliding layer contains MoS 2 and at least one of a Laves phase free bronze powder and a Laves phase free bronze powder.
[0017] A slide member according to a fifth aspect of the present invention is the slide member according to the first or second aspect, The resin composition is composed of copper sulfide, thermoplastic resin, molybdenum disulfide, graphite, aramid fibers, and the balance is fluororesin, and contains more than 3 mass% and less than 40 mass% of the copper sulfide, 0 mass% or more and less than 4 mass% of the thermoplastic resin, 0 mass% or more and 36 mass% or less of the molybdenum disulfide, 0 mass% or more and 10 mass% or less of the graphite, 0 mass% or more and 10 mass% or less of the aramid fibers, and the balance is the fluororesin.
[0018] A slide member according to a sixth aspect of the present invention is a slide member according to any one of the first to fifth aspects, The porous layer is A matrix phase containing Cu and Sn; and hard particles dispersed in the matrix phase, the hard particles including a Laves phase composed of Co, Mo and Si.
[0019] A slide member according to a seventh aspect of the present invention is the slide member according to the sixth aspect, The porous layer is The composition further comprises a compound phase dispersed in the matrix phase, the compound phase including Co, Fe, Ni, Si and Cr.
[0020] A slide member according to an eighth aspect of the present invention is a slide member according to any one of the first to seventh aspects, The ratio of the thickness of the porous layer to the thickness of the sliding layer is 6:4 to 8:2.
[0021] A bearing according to a ninth aspect of the present invention comprises: A cylindrical metal substrate; A porous layer formed on the inner circumferential surface of the metal substrate; A sliding layer is provided to cover the porous layer, The porous layer is formed of a metal or an alloy composition, The sliding layer is formed of a resin composition, The resin composition is not present on a part of the inner circumferential surface, and the non-porous layer formed of the metal element or alloy composition is exposed in the region.
[0022] A method for producing a slide member according to a tenth aspect of the present invention includes the steps of: forming a porous layer made of a metal element or an alloy composition on one surface of a metal substrate; rolling the metal substrate with the porous layer on the inside to form a cylindrical shape; a step of welding a joint portion from an outer diameter side of the metal substrate, the porous layer on the joint portion being melted to form a non-porous layer formed of the metal or alloy composition; a step of forming a sliding layer made of a resin composition by impregnating a surface of the porous layer with a raw resin of a sliding layer and baking the raw resin to cover the porous layer, wherein the surface of the non-porous layer is not impregnated with the raw resin, so that the resin composition is not present on a part of the inner circumferential surface of the sliding member, and a region where the non-porous layer is exposed is formed; Includes.
[0023] A method for producing a slide member according to an eleventh aspect of the present invention includes the steps of: forming a porous layer made of a metal element or an alloy composition on one surface of a metal substrate; a step of forming a sliding layer made of a resin composition by impregnating a surface of the porous layer with a raw material resin of a sliding layer and baking the raw material resin to cover the porous layer; rolling the metal substrate with the sliding layer on the inside to form a cylindrical shape; a step of welding a seam portion from an outer diameter side of the metal base material, in which the porous layer on the seam portion is melted to form a non-porous layer formed of the metal element or alloy composition, and the sliding layer on the seam portion is peeled off, thereby forming a region in which the resin composition is not present on a part of the inner circumferential surface of the sliding member and the non-porous layer is exposed; Includes.
[0024] A method according to a twelfth aspect of the present invention is a method according to the tenth or eleventh aspect, comprising: a step of burnishing an inner circumferential surface of the sliding layer by pressing a cylindrical core metal into the inside of the sliding layer while constraining an outer circumferential surface of the metal base material with a die; Further includes: Effect of the Invention
[0025] According to the present invention, it is possible to provide a slide member in which temperature rise in a high-speed rotation region is suppressed more than in the slide member proposed in Japanese Patent Application No. 2023-026107, and a method for manufacturing the slide member. [Brief description of the drawings]
[0026] [Figure 1] FIG. 1 is a perspective view showing a schematic configuration of a sliding member according to one embodiment. [Diagram 2] FIG. 2 is a photographic image of a welded portion of a sliding member according to one embodiment, taken from the outer periphery side. [Diagram 3] FIG. 3 is a photographic image of a region corresponding to a welded portion of a sliding member according to one embodiment, taken from the inner periphery side. [Figure 4] FIG. 4 is an optical microscope photograph of the cross-sectional structure of the area corresponding to the weld before the sliding layer is formed (resin impregnation and baking). [Diagram 5] FIG. 5 is a backscattered electron composition image of a cross-sectional structure of a region other than a welded portion of a slide member according to one embodiment. [Figure 6] FIG. 6 is a flow chart showing an example of a method for producing a slide member according to an embodiment. [Figure 7] FIG. 7 is a flow chart showing another example of the method for producing the slide member according to the embodiment. [Figure 8] FIG. 8 is a diagram for explaining the raw material powder scattering step and the porous layer sintering step. [Figure 9] FIG. 9 is a diagram for explaining the raw material resin impregnation step. [Figure 10] FIG. 10 is a diagram for explaining the burnishing process. [Figure 11] FIG. 11 is a diagram showing a schematic configuration of a high-speed rotation abrasion tester. [Figure 12] FIG. 12 is a diagram for explaining the position of the load point (load category A) during measurement in the high-speed rotation wear test for the sliding member according to the example. [Figure 13] FIG. 13 is a table showing the compositions and the like of the slide members according to the examples and comparative examples 1 to 3. [Figure 14] FIG. 14 is a graph showing the change over time in the bearing temperature measured for the sliding members according to the example and comparative examples 1 to 3 when the shaft rotation speed N was 15,000 rpm. [Figure 15] FIG. 15 is a graph showing the change over time in the bearing temperature measured for the sliding members according to the example and comparative examples 1 to 3 when the shaft rotation speed N was 20,000 rpm. [Figure 16] FIG. 16 is a graph showing the change over time in the bearing temperature measured for the sliding members according to the example and comparative examples 1 to 3 when the shaft rotation speed N was 25,000 rpm. [Figure 17]FIG. 17 is a graph showing the change over time in the bearing temperature measured for the sliding members according to the example and comparative examples 1 to 3 when the shaft rotation speed N was 30,000 rpm. [Figure 18] FIG. 18 is a graph showing the change over time in the bearing temperature measured for the sliding members according to the example and comparative example 1 when the shaft rotation speed N was 35,000 rpm. [Figure 19] FIG. 19 is a graph showing the change in temperature rise rate versus shaft rotation speed in the shaft rotation speed range of 10,000 to 50,000 rpm for the sliding members according to the example and comparative examples 1 to 3. [Figure 20] FIG. 20 is a graph showing the change in power consumption relative to the shaft rotation speed in the range of 10,000 to 50,000 rpm for the sliding members according to the example and comparative examples 1 to 3. [Figure 21] FIG. 21 is a graph showing the change in the rate of temperature rise with respect to the shaft rotation speed in the range near the shaft rotation speed at which a sudden increase in the rate of temperature rise and power consumption occurs for the sliding members according to the example and comparative examples 1 to 3. [Figure 22] FIG. 22 is a graph showing the change in power consumption with respect to the shaft rotation speed in the range near the shaft rotation speed at which a rapid increase in the temperature increase rate occurs for the sliding members according to the example and comparative examples 1 to 3. [Figure 23] FIG. 23 is a diagram for explaining the position of the load point (load category B) during measurement in a high-speed rotation wear test for the sliding member according to the example. [Figure 24] FIG. 24 is a graph showing the change in temperature rise rate versus shaft rotation speed measured in load categories A and B for the sliding member according to the example. [Diagram 25] FIG. 25 is a graph showing the change in power consumption with respect to the shaft rotation speed measured in load categories A and B for the sliding member according to the example. [Figure 26] FIG. 26 is a graph showing the inner diameter accuracy of the sliding member according to the example. [Figure 27] FIG. 27 is a graph showing the inner diameter accuracy of the sliding member according to Comparative Example 1. As shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Hereinafter, the embodiment of the present invention will be described in detail with reference to the attached drawings. In this specification, "%" regarding the composition means "mass %" unless otherwise specified. In this specification, "XX to △△" (○○ and △△ are both numbers) means "XX or more and △△ or less" unless otherwise specified. In this specification, "main component" refers to a component that is contained in an amount of 50 mass % or more of the entire composition. In this specification, "hard particle powder" refers to a powder in the mixed powder before sintering or a powder dispersed in the resin composition of the sliding layer, and "hard particles" refers to particles in the porous layer after sintering. As described later, Cu and Sn contained in the hard particle powder move to a certain extent into the matrix phase during sintering, so the content of the hard particles in the porous layer varies from the blending amount of the hard particle powder in the mixed powder, and the content of each constituent element in the hard particles is different from the content of each constituent element in the hard particle powder (hard particles are particles having a composition in which the content of Sn and Cu among chemical components is somewhat lower than that of the hard particle powder). In addition, in this specification, the term "seam" refers to a part that connects two objects (or two ends of one object) so that they are continuous, and includes both cases where the object is welded and cases where the object is not welded. In cases where the object is not welded, the term "seam" refers to both cases where two objects (or two ends of one object) are in contact and cases where the objects are separated by a small gap. Here, the "small gap" is not particularly limited in its specific width, as long as it can be regarded as being connected so that the objects are continuous when viewed as a whole, but it may be, for example, 1 / 10 or less of the entire length, 1 / 50 or less, or 1 / 100 or less. In this specification, a "seam" that is not welded may also be called a "joint".
[0028] <Configuration of sliding member> FIG. 1 is a perspective view showing a schematic configuration of a slide member 10 according to an embodiment. FIG. 2 is a photographic image of the welded portion of the slide member 10 taken from the outer periphery side, FIG. 3 is a photographic image of the region corresponding to the welded portion of the slide member 10 taken from the inner periphery side, and FIG. 4 is an optical microscope photograph of the cross-sectional structure of the region corresponding to the welded portion before the formation of the sliding layer (resin impregnation and baking). FIG. 5 is a backscattered electron composition image of the cross-sectional structure of the region other than the welded portion of the slide member according to an embodiment. In FIG. 4 and FIG. 5, the upper side of the paper corresponds to the inner periphery side of the slide member 10, and the lower side of the paper corresponds to the outer periphery side of the slide member 10.
[0029] 1 to 5, the sliding member 10 is, for example, a sliding bearing, and includes a cylindrical metal substrate 11, a porous layer 12 formed on the inner circumferential surface of the metal substrate 11, and a sliding layer 13 covering the porous layer 12. Of these, the porous layer 12 is formed of a simple metal or an alloy composition, and the sliding layer 13 is formed of a resin composition.
[0030] As shown in Fig. 1, a sliding member 10 serving as a plain bearing is adapted to support a shaft 20, which is a sliding object, with a sliding layer 13 forming a cylindrical inner peripheral surface. The inner diameter roundness of the sliding layer 13 may be 50 µm or less, or may be 20 µm or less. In this case, friction on the inner peripheral surface of the sliding layer 13 is reduced, thereby achieving further reduction in wear and heat generation.
[0031] The sliding member 10 is applicable whether the shaft 20 rotates or moves linearly. The sliding member 10 may be used in a sliding part in which oil is used in a linear motion, such as a shock absorber for an automobile. The sliding member 10 may also be used in a sliding part in which oil is used in a rotational motion, such as a gear pump that delivers oil by rotating a gear-shaped member. Each component of the sliding member 10 will be described in detail below.
[0032] 1 to 3, the metal base 11 has a cylindrical shape. The metal base 11 can be manufactured, for example, by rolling a metal plate material into a cylindrical shape and then welding a joint portion 11a (see FIG. 2). The material of the metal base 11 is not particularly limited as long as it has strength and shape stability sufficient to be used as a backing metal base material for a bearing, but may be, for example, low carbon steel (SPCC, SS400, etc.) or a copper-plated steel sheet in which an Fe-based plate material is plated with Cu.
[0033] The porous layer 12 has a cylindrical shape, and is formed by sintering metal powder (a mixed powder described below, or an alloy powder obtained by alloying the mixed powder during spraying) onto the surface of the metal base material 11. The thickness of the porous layer 12 may be a thickness that allows at least two or more particles of metal powder to be sintered together, and may be, for example, 0.5 mm or less.
[0034] The sliding layer 13 is formed by impregnating the porous layer 12 with a resin composition to a predetermined thickness, and baking the resin composition impregnated in the porous layer 12. The thickness of the sliding layer 13 (thickness from the surface of the metal substrate 11) may be set to be thicker on average than the thickness of the porous layer 12 so that the porous layer 12 is not exposed. The ratio of the thickness of the porous layer 12 to the thickness of the sliding layer 13 may be 6:4 to 8:2, and may be, for example, 7:3.
[0035] The resin composition of the sliding layer 13 contains a fluororesin as a main component. Examples of the fluororesin that can be used as the base resin of the resin composition include PTFE (polytetrafluoroethylene), PFA (perfluoroalkoxyalkane), FEP (perfluoroethylene-propylene copolymer), and EFFE (ethylene-tetrafluoroethylene copolymer).
[0036] The resin composition contains PTFE as a main component of the fluororesin, and may contain other fluororesins other than PTFE, such as PFA, as optional additives. The content of the other fluororesins contained as optional components may be 0 vol% or more and 20 vol% or less in the resin composition.
[0037] Commercially available PTFE resin products include Polyflon (registered trademark) D-210C and F-201 (manufactured by Daikin Industries, Ltd.), Fluon (registered trademark) AD911D (manufactured by Asahi Glass Co., Ltd.), and Teflon (registered trademark) 31JR and 6C-J (manufactured by Mitsui-DuPont Fluorochemicals Co., Ltd.).
[0038] 5, hard particle powder 13a including a Laves phase composed of Co, Mo, and Si may be dispersed in the resin composition of the sliding layer 13. Here, the Laves phase is an AB phase composed of elements A and B with an atomic radius ratio of about 1.2:1. 2 It is an intermetallic compound based on the MgZn 2 (C14) type, MgCu 2 (C15) type, MgNi 2 There are three types of structures of the (C36) type. The composition of Co, Mo and Si (more specifically, Co 3 Mo 2 The Laves phase, which is composed of MgZn 2 It is a type. 3 Mo 2 The Vickers hardness of the Laves phase composed of Si is Hv1000 to 1200. It is considered that the hard particle powder 13a dispersed in the sliding layer 13 receives a higher load than the resin composition forming the sliding layer 13, but the hard Laves phase composed of Co, Mo and Si precipitates on the friction surface and supports the load, which can be advantageous in reducing wear of the sliding layer 13.
[0039] In addition, Mo in the Laves phase and S in the lubricant form MoS on the friction surface. 2 A sulfide film of MoS can be formed. 2is a material known as a sulfide that substitutes for the solid lubrication of lead and contributes to improving friction characteristics, and since the bonds between sulfur are weaker than the bonds between molybdenum and between molybdenum and sulfur, when friction occurs, the bonds between sulfur are selectively broken, causing lubrication, which can be effective in suppressing wear. In addition, Mo oxides that are generated on the friction surface due to oxidation of Mo in the Laves phase during sliding also exert a lubricating effect and can be effective in suppressing wear.
[0040] The resin composition of the sliding layer 13 contains molybdenum disulfide (MoS 2 ) powder and Laves phase-free bronze powder. As described above, MoS 2 is a material known as a sulfide that replaces the solid lubrication of lead and contributes to improving friction characteristics. Compared to the bonds between molybdenum and between molybdenum and sulfur, the bonds between sulfur are weaker. When friction occurs, the bonds between sulfur are selectively broken, resulting in lubrication and can be effective in suppressing wear.
[0041] In one variation, the resin composition of the sliding layer 13 is made of copper sulfide (CuS), a thermoplastic resin, molybdenum disulfide (MoS 2 ), graphite, aramid fibers, and the remainder may be fluororesin (however, the resin composition does not contain lithium phosphate). In this case, the resin composition may contain more than 3 mass% and less than 40 mass% copper sulfide, 0 mass% or more and less than 4 mass% thermoplastic resin, 0 mass% or more and 36 mass% or less molybdenum disulfide, 0 mass% or more and 10 mass% or less graphite, 0 mass% or more and 10 mass% or less aramid fibers, and the remainder may be fluororesin.
[0042] The resin composition forming the slide layer 13 contains copper sulfide as a metal sulfide, thereby improving the heat dissipation characteristics of the slide layer 13. This suppresses a temperature rise in the slide layer 13 caused by the sliding of the sliding object, and suppresses deformation of the slide layer 13 due to the temperature rise.
[0043] Furthermore, by including copper sulfide in the resin composition forming the sliding layer 13, the strength of the sliding layer 13 is improved. It is known that by including a carbon fiber filler in the resin composition forming the sliding layer, the strength of the resin layer is improved. In contrast, by including copper sulfide in the resin composition, the strength is improved in the same way as when a carbon fiber filler is included, even if no carbon fiber filler is included. The improvement in the strength of the sliding layer 13 also suppresses the deformation of the sliding layer 5 due to the sliding of the sliding object.
[0044] When the deformation amount of the sliding layer 13 is large, the amount of wear increases compared to when the deformation amount is small. Therefore, by suppressing the deformation of the sliding layer 13, the wear of the sliding layer 13 is suppressed and the wear resistance property is improved. Furthermore, by improving the strength of the sliding layer 13, the wear is suppressed. Furthermore, by suppressing the wear of the sliding layer 13, the exposure of the porous layer 12 is suppressed, and the dry touch that is a cause of seizure and the like due to direct contact between the porous layer 12 and the sliding object can be suppressed, and the seizure resistance is improved.
[0045] Copper sulfide is cuprous sulfide (Cu 2 S) and cupric sulfide (CuS). 2 Cupric sulfide (CuS) is stable even at temperatures above 1000°C. In contrast, cupric sulfide (CuS) turns into cuprous sulfide (CuS) at temperatures around 200°C. 2 When polytetrafluoroethylene is used as the resin, the resin composition 4 is heated at a temperature exceeding 327° C. in the step of baking the slide layer 13. Therefore, when the resin composition contains cupric sulfide (CuS), the cupric sulfide (CuS) is changed to cuprous sulfide (CuS) in the step of baking the slide layer 13. 2 S).
[0046] As a result, the sliding layer 13 of the sliding member 10 produced contains copper(I) sulfide (Cu 2 However, the raw material for copper sulfide is cuprous sulfide (Cu 2 Although copper sulfide (CuS) or copper sulfide (CuS) may be used, it is preferable to use copper sulfide (CuS) from the viewpoint of workability.
[0047] By further including molybdenum disulfide as a metal sulfide in the resin composition forming the sliding layer 13, the sliding characteristics against a sliding object that slides in contact with the sliding layer 13 are improved. Furthermore, by including graphite in the resin composition forming the sliding layer 13, the sliding characteristics are also improved. As a result, with a configuration that does not include lead (Pb), sliding characteristics equivalent to those of a sliding member that includes Pb can be obtained. Hereinafter, the resin composition of the sliding layer 13 according to one modified example will be described in detail.
[0048] [Copper sulfide: more than 3% by mass and less than 40% by mass] The resin composition forming the sliding layer 13 preferably contains more than 8% by mass and less than 40% by mass of copper sulfide in order to improve heat dissipation characteristics and strength. If the amount of copper sulfide added is 3% by mass or less or 40% by mass or more, the heat dissipation characteristics deteriorate and the wear resistance characteristics are impaired. Commercially available products include cupric sulfide (CuS) manufactured by Terada Yakusen Kogyo Co., Ltd., cupric sulfide (CuS) manufactured by Kanto Kagaku Co., Ltd., and cuprous sulfide (CuS) manufactured by Kojundo Kagaku Kenkyusho Co., Ltd. 2 S) and the like.
[0049] [Plastic resin: 0% by mass or more and 4% by mass or less] In the resin composition of the sliding layer 13 according to one modified example, a thermoplastic resin is not an essential additive. However, when added, it is preferable to add the thermoplastic resin because it can improve the wear resistance and creep resistance properties, which are disadvantages of the fluororesin.
[0050] When the thermoplastic resin is added, if the amount exceeds 4 mass %, the low friction property of the fluororesin is impaired. Commercially available PPS resins as thermoplastic resins include PQ-208 manufactured by DIC Corporation and Fortron (registered trademark) KPS manufactured by Kureha Corporation.
[0051] [Graphite: 0 mass% or more and 10 mass% or less] In the resin composition of the sliding layer 13 according to one modification, graphite is not an essential additive, but it is expected to contribute to improving self-lubrication and heat resistance, and to low friction and wear resistance. When graphite is added in an amount exceeding 10 mass%, the low friction characteristics are impaired. Examples of commercially available graphite products include UCP and CPB manufactured by Nippon Graphite Industries Co., Ltd., and the AT series manufactured by Oriental Sangyo Co., Ltd.
[0052] [Molybdenum sulfide: 0% by mass or more and 36% by mass or less] In the resin composition of the sliding layer 13 according to one modification, molybdenum disulfide (MoS 2 ) is not an essential additive, but adding it can reduce frictional resistance.
[0053] If the amount of molybdenum disulfide added exceeds 36 mass%, the impregnation into the porous layer becomes poor during the impregnation process. 2 and the molybdenum disulfide powder series manufactured by Daizo Corporation.
[0054] [Aramid fiber: 0% to 10% by mass] In the resin composition of the sliding layer 13 according to one modified example, aramid fiber is not an essential additive, but is added to obtain mechanical strength. When 10% by mass or more of aramid fiber is added, uniform dispersion is hindered, resulting in a decrease in wear resistance. Examples of commercially available products include Kevlar (registered trademark) manufactured by DuPont-Toray Co., Ltd. and Twaron (registered trademark) manufactured by Teijin Co., Ltd.
[0055] In another modified example, the resin composition of the sliding layer 13 is a zinc compound (ZnS (zinc sulfide), ZnO (zinc oxide), ZnSO 4 (e.g. zinc sulfate), carbon fiber, iron oxide, barium sulfate, aramid fiber, graphite, calcium compounds (CaCO 3 (Calcium carbonate), CaSO 4 (Calcium sulfate), Ca(OH) 2The resin composition may contain any one or more of (calcium hydroxide, etc.), zinc, and zinc alloy as an optional additive. When the resin composition contains a zinc compound, the elastic modulus is improved, and deformation of the sliding layer 13 is suppressed, and the deformation of the sliding layer 13 due to an external force, which causes an increase or decrease in the contact area, can be suppressed. Furthermore, when the resin composition contains carbon fiber, the value of the kinetic friction force and the change between the static friction force and the kinetic friction force can be improved, and the sliding characteristics can be improved. When the resin composition contains iron oxide, the elastic modulus can be improved in addition to the wear resistance. When the resin composition contains barium sulfate or aramid fiber, the wear resistance can be increased without inhibiting the improvement of the elastic modulus by the addition of a zinc compound. When the resin composition contains graphite, the friction resistance can be reduced without inhibiting the improvement of the elastic modulus by the addition of a zinc compound. When the resin composition contains a calcium compound, zinc, or zinc alloy, the wear resistance can be improved without inhibiting the improvement of the elastic modulus by the addition of a zinc compound.
[0056] As a modified example, the porous layer 12 may have a matrix phase containing Cu and Sn and hard particles dispersed in the matrix phase. The porous layer 12 may be formed by sintering an alloy powder obtained by alloying the mixed powder when spraying. By making the powder into an alloy powder, the sintering of the powder is promoted to form a neck, and the powders can be sufficiently bonded to each other. By making the powder into an alloy powder, the hard particles are refined and uniformly dispersed in the matrix phase. Note that, when the hard particle powder 13a is dispersed in the above-mentioned sliding layer 13, the porous layer 13 may not contain hard particles.
[0057] The matrix phase is a bronze-based alloy containing Cu as a main component and further containing Sn. The matrix phase may be composed of a solid solution of Cu, Sn and Ni.
[0058] Bi particles may be distributed in the grain boundaries of the matrix phase. In this case, Bi exerts a self-lubricating effect similar to that of Pb in conventional lead bronze on the friction surface where the sliding layer 4 wears and part of the porous layer 3 is exposed, and acts as a lubricant between the two rubbing surfaces, thereby reducing friction.
[0059] The hard particles may contain a Laves phase composed of Co, Mo, and Si. When the sliding layer 13 wears and a part of the porous layer 12 is exposed, it is considered that the hard particles dispersed in the matrix phase are subjected to a higher load than the soft bronze that constitutes the matrix phase. However, the hard Laves phase composed of Co, Mo, and Si precipitates on the friction surface and supports the load, which can be advantageous in reducing wear of the porous layer 12. In addition, Mo in the Laves phase and S in the lubricating oil form MoS on the friction surface. 2 A sulfide film of MoS can be formed. 2 is a material known as a sulfide that substitutes for the solid lubrication of lead and contributes to improving friction characteristics, and since the bonds between sulfur are weaker than the bonds between molybdenum and between molybdenum and sulfur, when friction occurs, the bonds between sulfur are selectively broken, causing lubrication, which can be effective in suppressing wear. In addition, Mo oxides that are generated on the friction surface due to oxidation of Mo in the Laves phase during sliding also exert a lubricating effect and can be effective in suppressing wear.
[0060] When the porous layer 12 contains hard particles, the content of the hard particles may be, for example, 40% by mass or less when the entire porous layer 12 is taken as 100% by mass. When the entire porous layer 12 is taken as 100% by mass, the content of the hard particles may be, for example, 0.1% by mass or more. If the content of the hard particles is 0.1% by mass or more, the effect of reducing wear of the porous layer 12 as described above can be obtained. In addition, when the entire porous layer 12 is taken as 100% by mass, the content of the Laves phase composed of Co, Mo, and Si may be, for example, 0.1 to 20% by mass. When the hard particle powder 13a is dispersed in the above-mentioned sliding layer 13 and the porous layer 12 does not contain hard particles, the total content of Cu and Sn may be 99.9% or more when the entire porous layer 12 is taken as 100% by mass.
[0061] The porous layer 3 may further have a compound phase dispersed in the matrix phase. The compound phase may contain Co, Fe, Ni, Si, and Cr. The formation of the compound phase in the matrix phase can increase the hardness of the matrix phase, which can be advantageous in improving seizure resistance.
[0062] The sliding member 10 according to the present embodiment has four aspects: (1) a mode in which the porous layer 12 contains hard particles, but the sliding layer 13 does not contain hard particle powder 13a; (2) a mode in which the porous layer 12 does not contain hard particles, but the sliding layer 13 contains hard particle powder 13a; (3) a mode in which the porous layer 12 contains hard particles, and the sliding layer 13 contains hard particle powder 13a; and (4) a mode in which the porous layer 12 does not contain hard particles, and the sliding layer 13 does not contain hard particle powder 13a. In any of the modes (1) to (3), when the total of the porous layer 12 and the sliding layer 13 (i.e., the entire sliding member 10 excluding the metal substrate 11) is taken as 100 mass%, the total content of the hard particles and the content of the hard particle powder 13a may be 1 to 20 mass%, for example, 15 mass%.
[0063] As shown in Figs. 3 and 4, the slide member 10 has a region 15 where the resin composition is not present in a part of the inner circumferential surface, and a non-porous layer 14 (see Fig. 4) formed of a simple metal or an alloy composition is exposed. In the example shown in Fig. 3, only one region 15 where the resin composition is not present is provided on the inner circumferential surface of the slide member 10, but a plurality of regions may be provided. As shown in Fig. 3, the region 15 where the resin composition is not present may be provided so as to extend from one end to the other end in the axial direction of the slide member 10. The region 15 where the resin composition is not present may be provided on a seam portion 11a (see Fig. 2) of the metal substrate 11. The non-porous layer 14 may be formed of the same simple metal or alloy composition as the porous layer 12.
[0064] 4, the nonporous layer 14 has a recessed inner surface compared to the surrounding area because the metal or alloy composition constituting the porous layer 12 is melted. The depth D of the recessed space in the nonporous layer 14 may be, for example, 0.2 to 0.3 mm. The width (length in the circumferential direction) W of the nonporous layer 14 may be 0.1 to 10% of the inner circumferential length of the sliding member 10, and for example, when the inner circumferential length of the sliding member 10 is 60 to 70 mm, the width W of the nonporous layer 14 may be 1.0 mm to 3.0 mm.
[0065] <Method of manufacturing slide member> Next, an example of a method for manufacturing the slide member 10 having such a configuration will be described with reference to Fig. 6 and Figs. 8 to 10. Fig. 6 is a flow diagram showing an example of a method for manufacturing the slide member 10. Fig. 8 is a diagram for explaining the raw material powder scattering step and the porous layer sintering step. Fig. 9 is a diagram for explaining the raw material resin impregnation step, and Fig. 10 is a diagram for explaining the burnishing step.
[0066] As shown in FIGS. 6 and 8, first, raw material powder of the porous layer 12 is spread onto one surface of a plate-shaped metal substrate (step S10).
[0067] The raw material powder may be a first powder containing Cu and Sn, or a mixed powder obtained by mixing the first powder with a hard particle powder containing a Laves phase composed of Co, Mo and Si, or a mixed powder obtained by mixing the first powder, the hard particle powder and a second powder containing Cu, Co, Fe, Ni, Si and Cr in addition to the first powder and the hard particle powder.
[0068] Here, the first powder is a bronze-based alloy powder containing Cu as a main component and further containing Sn. The first powder may further contain Bi or P. When the first powder contains Bi, Bi particles are precipitated in the matrix phase 10 during sintering of the raw material powder described later (i.e., step S20), and Bi exhibits a self-lubricating effect similar to that of Pb in conventional lead bronze, so that friction can be reduced. When the first powder contains P, oxygen mixed in copper can be removed (deoxidized) to suppress hydrogen embrittlement. The content of each constituent element of the first powder may be Sn: 10 to 11 mass%, Cu: balance. When Bi is further contained, Bi: 7 to 9 mass%, and when P is contained, P: 0.02 mass% or less is preferable. The blending amount of the first powder in the raw material powder is the amount of the remainder obtained by subtracting the total blending amount of powders other than the first powder from the blending amount of the entire raw material powder.
[0069] The hard particle powder is an alloy powder containing Cu and a Laves phase composed of Co, Mo, and Si, and is a hard particle powder containing Cu, Si, Fe, Mo, Co, and Cr. The hard particle powder may further contain Sn, for example, 1 mass% or more of Sn. The solid-phase temperature of the hard particle powder not containing Sn reaches nearly 1450°C, but by including Sn, the solid-phase temperature of the hard particle powder can be reduced, and the hard particle powder can be solid-phase sintered to the backing metal base material at nearly 800°C. In addition, the Sn contained in the hard particle powder is dissolved in the Cu-Sn matrix phase side by the first powder during sintering, and is diffusion-bonded. As sintering progresses due to powder shrinkage via Sn, solid-solution strengthening by the Sn in the matrix phase and the Sn contained in the hard particle powder can be realized. The content of each element in the hard particle powder may be Co: 14-20 mass%, Mo: 24-28 mass%, Si: 3-7 mass%, Fe: 2-16 mass%, Cr: 1-10 mass%, and Cu: remainder, when the entire hard particle powder is taken as 100 mass%. In the case where Sn is included, the content of each element in the hard particle powder may be Co: 14-20 mass%, Mo: 24-28 mass%, Si: 3-7 mass%, Fe: 2-16 mass%, Cr: 1-10 mass%, Sn: 1-15 mass%, and Cu: remainder, when the entire hard particle powder is taken as 100 mass%. When the entire raw material powder is taken as 100 mass% (i.e., when the entire sliding layer 12 is taken as 100 mass%), the blending amount of the hard particle powder may be 1-40 mass%, and preferably 1-3 mass%. Since Cu and Sn are dissolved from the hard particle powder during sintering, the content of the hard particles in the sliding layer 12 varies depending on the blending amount of the hard particle powder in the raw material powder.
[0070] The second powder is an alloy powder containing Cu as a main component, and further containing Co, Fe, Ni, Si, and Cr. The second powder may further contain Sn, for example, 1 mass% or more of Sn. The solidus temperature of the second powder not containing Sn reaches nearly 1240°C, but by containing Sn, the solidus temperature of the second powder can be reduced, and the second powder can be solid-phase sintered to the back metal base material at nearly 800°C. When Sn is contained, the contents of each of the constituent elements in the second powder may be Co: 0.6 to 4.6 mass%, Fe: 1.6 to 5.6 mass%, Ni: 10 to 14 mass%, Si: 0.5 to 4.5 mass%, Cr: 0.5 to 1.5 mass%, Sn: 1 to 15 mass%, and Cu: balance, when the entire second powder is taken as 100 mass%. When the raw powder contains the second powder, the amount of the second powder may be 2 to 38 mass%, preferably 10 to 38 mass%, and more preferably 17 to 19 mass%, when the entire raw powder is taken as 100 mass%.
[0071] When the entire raw material powder is taken as 100% by mass, the blending amount of the hard particle powder may be 1 to 40% by mass, and the blending amount of the second powder may be 15 to 18% by mass, in which case excellent shear processability can be achieved.
[0072] The first powder, the hard particle powder, and the second powder can each be produced by, for example, spraying using a gas atomization method. In the gas atomization method, the heat source for melting may be high frequency, and a zirconia crucible (with a nozzle at the bottom) may be used.
[0073] The particle size of the first powder may be, for example, 45 μm to 180 μm. The particle size of the hard particle powder may be a fine powder of 53 μm or less. The particle size of the second powder may be 53 μm to 150 μm. Here, "particle size" refers to the particle size distribution measured by a laser diffraction / scattering method using a particle size distribution measuring device MT3300EXII manufactured by Microtrack Bell. This measurement method is a measurement method that conforms to the test procedure after the process of extracting powder from paste in "4.2.3 Laser diffraction type particle size distribution measurement test" of JIS Z3284-2.
[0074] Next, the raw powder scattered on the metal substrate 11 is sintered at 800 to 900°C to form the porous layer 12 (step S20). As described above, the solid-phase temperatures of the hard particle powder and the second powder that do not contain Sn reach approximately 1450°C and 1240°C, respectively. However, by including Sn, the solid-phase temperatures of the hard particle powder and the second powder can be reduced, and the hard particle powder and the second powder can be solid-phase sintered to the metal substrate (backing metal base material) at approximately 800°C. In addition, the Sn contained in the hard particle powder is dissolved in the Cu-Sn matrix phase 10 by the first powder during sintering, and is diffusion-bonded. As the sintering progresses due to the powder shrinkage via Sn, solid-solution strengthening by the Sn in the matrix phase 10 and the Sn contained in the hard particle powder is realized, and finally, a high-strength alloy can be formed.
[0075] Next, the metal substrate 11 is rolled up with the porous layer 12 on the inside to be shaped into a cylinder (step S30), and the seam portion 11a is welded from the outer diameter side of the metal substrate 11 (step S40). The welding method may be TIG welding (argon gas welding) or laser welding (pulse welding). At this time, the porous layer 12 above the seam portion 11a is melted by the heat during welding, and a large number of voids contained in the porous layer 12 are crushed, and a non-porous layer 14 formed of a simple metal or an alloy composition is formed. No seam appears on the inner diameter surface. In the non-porous layer 14, the apparent volume is reduced by the amount of the voids contained in the porous layer 12, so that the inner diameter surface has a concave shape compared to the surrounding porous layer 12.
[0076] Although not necessarily required, after the process of welding the seam portion 11a (step S40), the inner surface of the porous layer 12 may be burnished by pressing a cylindrical core metal 42 into the inside of the porous layer 12 while restraining the outer surface of the metal substrate 11 with a die 41 (see FIG. 10).
[0077] Next, the surface of the porous layer 12 is impregnated with the raw material resin of the sliding layer 13 (step S50). Specifically, for example, as shown in FIG. 9, a predetermined amount of resin composition may be supplied onto the porous layer 12 formed on the inner circumferential surface of the metal substrate 11, and the resin composition may be pressed against the porous layer 12 by the rotation pressure of an impregnation roll, thereby impregnating the porous layer 12 with the resin composition. The resin composition supplied onto the porous layer 12 may contain hard particle powder 13a including a Laves phase composed of Co, Mo, and Si, and molybdenum disulfide (MoS 2 ) powder may be dispersed in the resin composition. As a modified example, the resin composition may contain copper sulfide as an additive, and may further contain molybdenum disulfide, or may contain graphite and aramid fiber as other additives. The amount of the resin composition supplied onto the porous layer 12 is an amount that covers the porous layer 12 to a thickness that does not expose the porous layer 12 from the surface of the sliding layer 13 after the resin composition is baked as described below.
[0078] At this time, since the metal element or alloy composition constituting the porous layer 12 has melted, the surface of the non-porous layer 14 is not in a state where the raw material resin is impregnated between the pores, but rather the raw material resin is simply placed on the non-porous layer 14.
[0079] Next, the resin composition is heated at a temperature exceeding the melting point of the resin contained in the resin composition to melt the resin and volatilize the organic solvent, and then the resin is cured to form the sliding layer 13 made of the resin composition that covers the porous layer 12 (step S60). Forming the sliding layer 13 by heating the resin composition at a predetermined temperature is called baking. The melting point of polytetrafluoroethylene used as the resin is 327°C. The sliding layer 13 may be baked by heating the resin composition at a temperature exceeding the melting point of polytetrafluoroethylene (for example, 400 to 500°C) using a baking furnace.
[0080] At this time, since the surface of the nonporous layer 14 is in a melted state due to welding, the resin composition is easily peeled off from the top of the nonporous layer 14. After the formation of the sliding layer 13, the resin composition may be peeled off from the top of the nonporous layer 14 in a non-contact manner by gravity or wind force, or may be peeled off by sweeping with a brush or the like. By peeling off the resin composition from the top of the nonporous layer 14, a region 15 where the resin composition is not present on a part of the inner circumferential surface and the nonporous layer 14 is exposed is formed.
[0081] 10, while the outer peripheral surface of the metal base material 11 is restrained by a die 41, a cylindrical core metal 42 is pressed into the inside of the sliding layer 13, thereby burnishing the inner peripheral surface of the sliding layer 13 to set the inner diameter roundness to 50 μm or less (step S70). In this way, the sliding member 10 (see FIGS. 1 to 5) having the above-mentioned configuration is manufactured.
[0082] Next, another example of a method for producing the slide member 10 will be described with reference to Fig. 7. Fig. 7 is a flow chart showing another example of a method for producing the slide member 10.
[0083] As in the example of the manufacturing method described above, first, raw material powder for the porous layer 12 is scattered on one surface of the metal substrate (step S10), and then the raw material powder scattered on the metal substrate 11 is sintered to form the porous layer 12 (step S20).
[0084] 7, a predetermined amount of resin composition is supplied onto the porous layer 12, and the resin composition is pressed against the porous layer 12 to impregnate the porous layer 12 with the resin composition (step S150). The amount of the resin composition supplied onto the porous layer 12 is an amount that covers the porous layer 12 to a thickness that prevents the porous layer 12 from being exposed from the surface of the sliding layer 13 after the resin composition is baked, which will be described later.
[0085] Next, the resin composition is heated at a temperature exceeding the melting point of the resin contained in the resin composition to melt the resin and volatilize the organic solvent, and then the resin is hardened to form a sliding layer 13 made of the resin composition that covers the porous layer 12 (step S160).
[0086] Next, the metal base 11 is rolled up with the sliding layer 13 on the inside to be shaped into a cylinder (step S130), and the seam 11a is welded from the outer diameter side of the metal base 11 (step S140). The welding method may be TIG welding (argon gas welding) or laser welding (pulse welding). At this time, the porous layer 12 on the seam 11a melts due to the heat during welding, and many voids contained in the porous layer 12 are crushed to form a non-porous layer 14 formed of a simple metal or an alloy composition, and the resin composition on the seam 11a peels off, forming a region 15 where the resin composition is not present on a part of the inner circumferential surface and the non-porous layer 14 is exposed.
[0087] 10, while the outer peripheral surface of the metal base material 11 is restrained by a die 41, a cylindrical core metal 42 is pressed into the inside of the sliding layer 13, thereby burnishing the inner peripheral surface of the sliding layer 13 to set the inner diameter roundness to 50 μm or less (step S70). In this way, the sliding member 10 (see FIGS. 1 to 5) having the above-mentioned configuration is manufactured.
[0088] According to the embodiment described above, the resin composition is not present in a part of the inner circumferential surface of the sliding member 10, and the region 15 in which the non-porous layer 14 formed of a metal element or an alloy composition is exposed is provided. The region is recessed compared to the surrounding area because the resin composition is not present in the surrounding area and the non-porous layer does not contain many voids like the porous layer, and plays a role like a groove. When the sliding member 10 is used, the inner surface of the groove does not contact the shaft that is the sliding object, which contributes to reducing heat generation due to friction. This suppresses temperature rise in the high-speed rotation area and improves the performance of the bearing itself. In particular, when lubricating oil or grease is present, the oil film formation on the sliding surface is maintained by the groove, so that further heat reduction is expected compared to use in a dry environment.
[0089] In addition, the resin composition is not present on a part of the inner circumferential surface of the sliding member 10, and an area 15 is provided where a non-porous layer 14 formed of a metal or alloy composition is exposed, and no protrusions due to seams appear on the sliding surface, reducing the torque generated by friction at the seams. This contributes to reducing power consumption and energy loss, and therefore contributes to carbon neutrality.
[0090] Furthermore, for bearings used in high-speed rotation environments such as EV motors and electric compressors, it will be possible to replace conventional rolling bearings with the sliding member 10 according to this embodiment, leading to size and weight reduction.
[0091] Furthermore, when a conventional sliding member having a seam on the sliding surface is applied to a motor or a compressor, an inner diameter cutting process (i.e., surface alignment of the inner surface at the seam portion) is required. However, in the sliding member 10 according to the present embodiment, the resin composition is not present on a part of the inner circumferential surface of the sliding member 10, and a region 15 is provided where the non-porous layer 14 formed of a simple metal or an alloy composition is exposed. Therefore, no protrusions due to the seam appear on the sliding surface, and the inner diameter cutting process can be eliminated.
[0092] According to this embodiment, the region 15 where the resin composition is not present is provided so as to extend from one end to the other end in the axial direction of the slide member 10, so that the effect of reducing heat generation due to friction can be obtained continuously from one end to the other end in the axial direction. This makes it possible to further suppress the temperature rise in the high-speed rotation region.
[0093] Moreover, according to the present embodiment, the region 15 where the resin composition is not present has a recessed shape compared to the surrounding area and serves as a groove. The region 15 is formed by heat generated during welding of the seam portion 11a of the metal base material 11 at the same time. This makes it possible to reduce the number of steps compared to the case where the sliding layer is formed and then processed into an uneven shape.
[0094] <Example> Next, a specific example according to the present embodiment will be described.
[0095] (Production of sliding members) First, bronze powder (irregular shape, brand: CP-301) manufactured by Fukuda Metal Foil & Powder Co., Ltd. was prepared by removing coarse powder having a particle size of 150 μm or more as the raw material powder for the porous layer 12. The chemical composition of the bronze powder was Cu-10Sn.
[0096] Next, as an example, the raw material powder of the porous layer 12 was scattered on a copper-plated steel sheet, and then sintered at 880°C to form the porous layer 12. Next, in order to obtain an inner diameter dimension of Φ20 mm, the steel sheet on which the porous layer 12 was formed was slit to a slit width of 67.6 mm. Next, the slit-processed steel sheet was shaped into a cylindrical shape from the width direction while applying pressure via a side roll, and the seam portion of the steel sheet was argon gas welded from the outer diameter side. After welding, the sheet was shaped by water cooling, deburring, and sizing, and cut to a total length of 10 mm to obtain a cylindrical metal base material 11 on whose inner circumferential surface the porous layer 12 was formed. Then, referring to FIG. 10, an Amsler tester was used to apply a load to the inner circumferential surface of the porous layer 12 by pressing a core metal 42 into the inside of the porous layer 12 while restraining the outer circumferential surface of the metal base material 11 with a die 41, thereby correcting the inner circumferential surface of the porous layer 12 (burnishing).
[0097] Next, the inner circumferential surface of the porous layer 12 was impregnated with a resin. The composition of the impregnated resin was 1.1 mass% graphite powder, 15 mass% hard particle powder containing a Laves phase composed of Co, Mo, and Si, and the remainder PTFE resin, with MoS being added for the purpose of improving self-lubrication. 2 Powder: 15% by mass was added. The chemical composition of the hard particle powder was Cu-4.5Sn-5Si-15Fe-16Co-4Cr-26Mo, the particle size was under 53 μm, and the graphite powder was made by Nippon Graphite Co., Ltd. (brand: CPBW-5).
[0098] 9, the resin was applied to the inner peripheral surface of the porous layer 12 with a spatula, and while pressing with a rolling core metal of Φ11.7, the resin was impregnated into the porous layer 12 by the rotation pressure of the rolling. After that, the product was fired in a firing furnace under the conditions of a firing temperature of 480° C. and a conveyor speed of 1000 mm / min.
[0099] Next, referring to FIG. 10, an Amsler testing machine was used to apply a load to the inner peripheral surface of the sliding layer 13, thereby correcting the inner peripheral surface of the sliding layer 13 (burnishing) by pressing a core bar 42 into the inside of the sliding layer 13 while restraining the outer peripheral surface of the metal substrate 11 with a die 41.
[0100] The sliding member according to the embodiment was obtained by the above manufacturing process. The sliding member according to the embodiment has a weld mark on the outer peripheral surface of the metal substrate 11 extending from one end to the other end in the axial direction of the sliding member 10, and a region 15 in which the non-porous layer 14 in which no resin composition is present is exposed on the inner peripheral surface behind the weld mark, extending from one end to the other end in the axial direction of the sliding member 10. FIG. 26 is a graph showing the inner diameter measured at angles of 90°, 180°, 270°, and 360° in the circumferential direction for the sliding member according to the embodiment. As shown in FIG. 26, the inner diameter precision of the sliding member according to the embodiment was 0.018 mm or less.
[0101] In addition, the sliding members according to Comparative Examples 1 and 2 were produced by the manufacturing process described in Japanese Patent Application No. 2023-026107. That is, as Comparative Example 1, a carbon steel round bar was machined by a lathe to an outer diameter of Φ22 mm, an inner diameter of Φ20.62 mm, and a total length of 10.35 mm to obtain a seamless thin-walled cylindrical metal base material. As Comparative Example 2, a carbon steel plate material having a length of 67 mm, a width of 11 mm, and a thickness of 0.75 mm was machined into a rolled bushing to obtain a cylindrical metal base material having a seam of 2 mm or less in width (seam type).
[0102] Next, for Comparative Example 1, referring to Figures 5 and 6A of Japanese Patent Application No. 2023-026107, a carbon steel jig with an outer diameter of Φ19.96 mm was inserted into a metal substrate with an inner diameter of Φ20.62, and the same bronze powder as in the Example was poured into the gap of 0.3 mm between the inner surface of the metal substrate and the outer surface of the jig. The powder filling volume was 0.21 cm because the inner diameter of the metal substrate was Φ20.6 mm, the outer diameter of the jig was Φ19.96 mm, and the total length was 10.35 mm. 3For Comparative Example 2, refer to FIG. 6B of Japanese Patent Application No. 2023-026107. After the metal substrate was pressed into the inside of the housing to bring the seam (joint) into close contact, a carbon steel jig was coaxially arranged inside the metal substrate pressed into the housing, and the same bronze powder as in the Example was poured into the annular gap of 0.3 mm between the inner peripheral surface of the metal substrate and the outer peripheral surface of the jig. In both Examples 1 and 2, in order to improve the fluidity of the powder poured into the gap, a rotating shaft was connected to the jig and the powder was filled while rotating the jig by a motor. In this state, sintering was performed in a sintering furnace under the conditions of a sintering temperature of 880° C. and a conveyor speed of 230 mm / min.
[0103] Next, for Comparative Examples 1 and 2, the inside of a cylindrical metal substrate in which bronze powder was sintered was impregnated with resin. The composition of the impregnated resin was 1.1 mass% graphite powder, 15 mass% hard particle powder containing a Laves phase composed of Co, Mo, and Si, and the remainder PTFE resin, with MoS being added for the purpose of improving self-lubrication. 2 Powder: 15 mass% was added. The chemical composition of the hard particle powder is Cu-4.5Sn-5Si-15Fe-16Co-4Cr-26Mo, the particle size is 53μm or less fine powder, and the graphite powder is made by Nippon Graphite Co., Ltd. (brand: CPBW-5). The resin impregnation method is the same as in the above-mentioned embodiment, so the explanation is omitted.
[0104] Next, in the same manner as in the above-described embodiment, an Amsler testing machine was used to apply a load to the inner peripheral surface of the sliding layer 13, thereby correcting it (burnishing it) by pressing a core bar 42 into the inside of the sliding layer while restraining the outer peripheral surface of the metal substrate with a die 41.
[0105] The sliding members according to Comparative Examples 1 and 2 were obtained by the above manufacturing process. Fig. 27 is a graph showing the inner diameters of the sliding member according to Comparative Example 1 measured at angles of 90°, 180°, 270°, and 360° in the circumferential direction. As shown in Fig. 27, the inner diameter precision of the sliding members according to the Examples was 0.037 mm or less. It is presumed that the powder filling method in which bronze powder particles are filled one by one and sintered, as in Comparative Examples 1 and 2, results in a larger variation in the inner diameter compared to the method in which bronze powder is sintered and then shaped into a cylindrical shape, as in the Examples.
[0106] In addition, as Comparative Example 3, the same bronze powder as in the Example and Comparative Examples 1 and 2 was spread on a carbon steel plate material (metal substrate) and sintered to form a porous layer. Next, graphite powder: 4 mass%, MoS 2 The porous layer was impregnated with a resin consisting of 7.25% by mass of powder and the remainder being PTFE resin, and then the resin was baked to form a sliding layer covering the porous layer, followed by rolling. Next, the rolled metal substrate was processed into a rolled bushing shape with the sliding layer on the inside, thereby producing a sliding member in which the metal substrate, the porous layer, and the sliding layer all had seams (joints).
[0107] FIG. 13 is a table showing the compositions and other information of the slide members according to the example and comparative examples 1 to 3 produced by the above-mentioned procedure.
[0108] (High speed rotation wear test) Next, the performance of the sliding members of the embodiment and comparative examples 1 to 3 was compared by a high-speed rotation wear test. Figure 11 shows a high-speed rotation wear tester. This tester measures the temperature of the bearing back when a load and speed are applied to the test material via a mating shaft, and is mainly suitable for evaluating the amount of wear and heat generation in the high-speed range. An oil bath is provided in the test section, and the tester is designed to enable evaluation in both oil and non-lubricated environments. In order to realize high-speed evaluation, a spindle motor (model S262B-SJ03, rated output 1.2kW, rated voltage 200V, rated current 4.8A) manufactured by Shino Electric Co., Ltd. was directly connected to the tip of the mating shaft Φ6h7 via a collect chuck. This allows the device to be designed to evaluate up to a maximum of 60,000 rpm with an accuracy of 0.002 mm or less of shaft runout. The spindle motor is water-cooled via a chiller at a flow rate of 0.7 L / min.
[0109] The outer diameter of the mating shaft is Φ11.957mm~11.975mm, and the inner diameter of the housing is Φ14.000mm~14.018mm. Both are made of SKD-11 material, and the hardness after full quenching is HRC58. The temperature of the back surface of the bearing was measured every second with a data logger by inserting a thermocouple into a Φ6mm hole and measuring a position 1.5mm from the back surface of the bearing.
[0110] Next, regarding the test environment, the presence or absence of lubrication to the bearings has a large impact on performance. For example, in an air conditioning compression mechanism such as a compressor for a car air conditioner, in an environment where the orbiting scroll is strongly pressed against the fixed scroll while rotating, it is difficult for the lubricating oil to flow into the bearings. Furthermore, in order to achieve both compactness and lightness and high output at the same time, high speed rotation is essential for the drive motor of an EV. Oil-lubricated bearings and grease-lubricated bearings are used for the bearings that support the motor, but due to the simplification of the surrounding structure, oil lubrication of the bearings cannot be expected very much. In consideration of these practical constraints, this test was evaluated in an unlubricated environment, and frictional heat generation and wear amount were measured against the number of rotations of the shaft. The frictional heat generation was evaluated by the bearing temperature rise rate as an evaluation index, and the temperature slope against the time until the bearing back temperature reached 80°C was analyzed by regression analysis. The wear amount was obtained by measuring the thickness of the sliding members before and after the test with a pipe micrometer and calculating the thickness change at the load point.
[0111] The shaft rotation speed is said to reach a maximum of 10,000 rpm for the compressor's main shaft and a maximum of about 30,000 rpm for the EV motor. Taking this into consideration, the range was set to 10,000 to 50,000 rpm. A radial load of 10 N was applied to the bearing in one direction, taking into consideration the usage limit of the spindle motor at high speed rotation and safety. The target clearance between the bearing and the shaft was set to 0.1 mm, and the shaft was polished to a surface roughness of Ra0.17μm before being used for testing.
[0112] In the sliding member according to the embodiment, a region 15 where no resin composition is present is provided on a part of the inner circumferential surface, and as shown in FIG. 12, a position 90° away from the region 15 in the circumferential direction was set as a load point (hereinafter, the position of this load point is referred to as load category A).
[0113] Regarding the friction torque caused by rotational motion, the power can be converted into electric power, and can be expressed as in the following equation (1). E=P=2π·N·T / 60=2π·N·F·R / 60...Equation (1) Here, R is the radius of rotation (m), F is the frictional force (N), N is the shaft rotation speed (rpm), T is the torque (N m), E is the power (W), and P is the power rate (W).
[0114] (Results and Discussion) FIG. 14 is a graph showing the change over time in the bearing back temperature measured when the shaft rotation speed N is 15,000 rpm for the sliding members of the embodiment and comparative examples 1 to 3, FIG. 15 is a graph showing the change over time in the bearing back temperature measured when the shaft rotation speed N is 20,000 rpm, FIG. 16 is a graph showing the change over time in the bearing back temperature measured when the shaft rotation speed N is 25,000 rpm, FIG. 17 is a graph showing the change over time in the bearing back temperature measured when the shaft rotation speed N is 30,000 rpm, and FIG. 18 is a graph showing the change over time in the bearing back temperature measured when the shaft rotation speed N is 35,000 rpm.
[0115] 14 to 16, in the high speed rotation region of shaft rotation speed N=15,000 to 30,000 rpm, the change in temperature with time of the slide member according to the example behaves similarly to the change in temperature with time of the slide members according to comparative examples 1 and 2. Therefore, it was confirmed that in the high speed rotation region of shaft rotation speed N=15,000 to 30,000 rpm, the slide member according to the example retains the same function as the slide members according to comparative examples 1 and 2 (i.e., the slide members proposed in Japanese Patent Application No. 2023-026107).
[0116] 17 and 18, in the high speed rotation region of shaft rotation speed N=30,000 rpm or more, the temperature change of the sliding member according to the embodiment is more gradual than the temperature change of the sliding members according to comparative examples 1 and 2. Therefore, it was confirmed that the temperature rise of the sliding member according to the embodiment is suppressed more than that of the sliding parts according to comparative examples 1 and 2 (i.e., the sliding members proposed in Japanese Patent Application No. 2023-026107) particularly in the high speed rotation region of shaft rotation speed N=30,000 rpm or more.
[0117] FIG. 19 is a graph showing the change in temperature rise rate versus shaft rotation speed in the range of 10,000 to 50,000 rpm for the sliding members according to the example and comparative examples 1 to 3, and FIG. 20 is a graph showing the change in power consumption versus shaft rotation speed in the same range.
[0118] 19 and 20, the shaft rotation speed at which the temperature rise rate and power consumption suddenly increase is 15,000 rpm for the sliding member according to Comparative Example 3, 25,000 rpm for the sliding member according to Comparative Example 2, and 30,000 rpm for the sliding member according to Comparative Example 1, while it is 35,000 rpm for the sliding member according to the example. Therefore, it was confirmed that the sliding member according to the example has a higher allowable limit rotation speed than the sliding members according to Comparative Examples 1 to 3.
[0119] Furthermore, an additional evaluation test was conducted in which the rotation speed was changed finely in the range close to the shaft rotation speed where the temperature rise rate and power consumption suddenly increase. Fig. 21 is a graph showing the change in the temperature rise rate with respect to the shaft rotation speed in the range close to the shaft rotation speed where the temperature rise rate and power consumption suddenly increase for the sliding members according to the example and comparative examples 1 to 3, and Fig. 22 is a graph showing the change in power consumption with respect to the shaft rotation speed in the same range.
[0120] As shown in Fig. 21 and Fig. 22, the temperature rise rate and power consumption of the sliding member according to Comparative Example 3 are almost constant in the shaft rotation speed range of 7,000 to 8,000 rpm, and rise sharply when the shaft rotation speed exceeds 8,000 rpm, so that the allowable limit rotation speed can be determined to be 8,000 ± 1,000 rpm. The temperature rise rate and power consumption of the sliding member according to Comparative Example 2 are almost constant in the shaft rotation speed range of 22,000 to 25,000 rpm, and rise sharply when the shaft rotation speed exceeds 25,000 rpm, so that the allowable limit rotation speed can be determined to be 23,500 ± 1,500 rpm. The temperature rise rate and power consumption of the sliding member according to Comparative Example 1 are almost constant in the shaft rotation speed range of 27,000 to 30,000 rpm, and rise sharply when the shaft rotation speed exceeds 30,000 rpm, so that the allowable limit rotation speed can be determined to be 28,500 ± 1,500 rpm. In contrast, for the sliding member according to the embodiment, the temperature rise rate and power consumption are almost constant in the shaft rotation speed range of 30,000 to 33,000 rpm, but rise sharply above 33,000 rpm, so the allowable limit rotation speed can be determined to be 31,500±1,500 rpm.
[0121] Next, in order to investigate the influence of region 15, which is a part of the inner circumferential surface where the resin composition is not present, on the effect of suppressing a temperature rise, an additional evaluation test was conducted on the sliding member of the embodiment, in which a position that coincides with region 15 in the circumferential direction was set as a load point, as shown in FIG. 23 (hereinafter, the position of this load point is referred to as load category B).
[0122] FIG. 25 is a graph showing the change in temperature rise rate versus shaft rotation speed measured in load categories A and B for the sliding member according to the example, and FIG. 26 is a graph showing the change in power consumption versus shaft rotation speed.
[0123] 25 and 26, in the shaft rotation speed range of 30,000 to 33,000 rpm, load categories A and B have almost the same temperature rise rate and power consumption changes, but in the shaft rotation speed range of 33,000 rpm or more, load category A has a higher temperature rise rate and power consumption than load category B. In load category A, the temperature rise occurs due to the accumulation of frictional heat at the contact area, whereas in load category B, it is presumed that the frictional heat at the contact area is mitigated by the grooves in region 15 where no resin composition is present, making it easier to dissipate, thereby suppressing the temperature rise.
[0124] Although the embodiment and modified examples of the present invention have been described above by way of example, the scope of the present invention is not limited to these, and can be modified or changed according to the purpose within the scope of the claims. Furthermore, each embodiment and modified example can be appropriately combined within a range that does not cause contradiction in the processing content. [Explanation of symbols]
[0125] 10 Sliding member 11 Metal substrate 12 Porous layer 13 Sliding layer 14 Non-porous layer 15 Region where resin composition does not exist 13a hard particle powder 20 Axis 31 Jig 32 Rotation axis 33 Work 41 Dice 42 Core
Claims
1. A cylindrical metal substrate; A porous layer formed on the inner circumferential surface of the metal substrate; A sliding layer is provided to cover the porous layer, The porous layer is formed of a metal or an alloy composition, The sliding layer is formed of a resin composition, The resin composition is not present in a part of the inner circumferential surface, and the non-porous layer formed of the metal element or alloy composition is exposed in the part. A sliding member characterized by:
2. The region is provided so as to extend from one end to the other end in the axial direction of the sliding member.
2. The sliding member according to claim 1.
3. In the sliding layer, hard particle powder containing a Laves phase composed of Co, Mo and Si is dispersed.
3. The sliding member according to claim 1 or 2.
4. The sliding layer contains MoS 2 and at least one of the Laves phase-free bronze powder and the Laves phase-free bronze powder.
4. The sliding member according to claim 3.
5. The resin composition is composed of copper sulfide, a thermoplastic resin, molybdenum disulfide, graphite, aramid fibers, and the remainder is a fluororesin, and contains more than 3 mass% and less than 40 mass% of the copper sulfide, 0 mass% or more and less than 4 mass% of the thermoplastic resin, 0 mass% or more and 36 mass% or less of the molybdenum disulfide, 0 mass% or more and 10 mass% or less of the graphite, 0 mass% or more and 10 mass% or less of the aramid fibers, and the remainder is the fluororesin.
3. The sliding member according to claim 1 or 2.
6. The porous layer is A matrix phase containing Cu and Sn; and hard particles dispersed in the matrix phase, the hard particles including a Laves phase having a composition of Co, Mo and Si.
3. The sliding member according to claim 1 or 2.
7. The porous layer is The composite material further comprises a compound phase dispersed in the matrix phase, the compound phase including Co, Fe, Ni, Si, and Cr.
7. The sliding member according to claim 6.
8. The ratio of the thickness of the porous layer to the thickness of the sliding layer is 6:4 to 8:
2.
3. The sliding member according to claim 1 or 2.
9. A cylindrical metal substrate; A porous layer formed on the inner circumferential surface of the metal substrate; A sliding layer is provided to cover the porous layer, The porous layer is formed of a metal or an alloy composition, The sliding layer is formed of a resin composition, The resin composition is not present in a part of the inner circumferential surface, and the non-porous layer formed of the metal element or alloy composition is exposed in the part. A bearing comprising:
10. A method for manufacturing a slide member, comprising the steps of: forming a porous layer made of a metal element or an alloy composition on one surface of a metal substrate; rolling the metal substrate with the porous layer on the inside to form a cylindrical shape; a step of welding a joint portion from an outer diameter side of the metal substrate, the porous layer on the joint portion being melted to form a non-porous layer formed of the metal or alloy composition; a step of forming a sliding layer made of a resin composition by impregnating a surface of the porous layer with a raw resin of a sliding layer and baking the raw resin to cover the porous layer, wherein the surface of the non-porous layer is not impregnated with the raw resin, so that the resin composition is not present on a part of the inner circumferential surface of the sliding member, and a region where the non-porous layer is exposed is formed; The method according to claim 1, further comprising:
11. A method for manufacturing a slide member, comprising the steps of: forming a porous layer made of a metal element or an alloy composition on one surface of a metal substrate; a step of forming a sliding layer made of a resin composition by impregnating a surface of the porous layer with a raw material resin of a sliding layer and baking the raw material resin to cover the porous layer; rolling the metal substrate with the sliding layer on the inside to form a cylindrical shape; a step of welding a seam portion from an outer diameter side of the metal base material, in which the porous layer on the seam portion is melted to form a non-porous layer formed of the metal element or alloy composition, and the sliding layer on the seam portion is peeled off, thereby forming a region in which the resin composition is not present on a part of the inner circumferential surface of the sliding member and the non-porous layer is exposed; The method according to claim 1, further comprising:
12. a step of burnishing an inner circumferential surface of the sliding layer by pressing a cylindrical core metal into the inside of the sliding layer while constraining an outer circumferential surface of the metal base material with a die; The method according to claim 10 or 11, further comprising:
Citation Information
Patent Citations
Oil-impregnated sintered bearing
JP2002039183A
Slide member and bearing
JP2018071710A
Sintered metal bearing, shaft member for a plain bearing unit, and plain bearing unit provided with said shaft member
WO2010134458A1
Rolling bearing
JP2018179049A
